Diverse Lithologies and Alteration Events on the Rim of Noachian‐Aged Endeavour Crater, Meridiani Planum, Mars: In Situ Compositional Evidence. Issue 5 (24th May 2018) - Mittlefehldt, David W.; Gellert, Ralf; vanBommel, Scott; Ming, Douglas W.; Yen, Albert S.; Clark, Benton C.; Morris, Richard V.; Schröder, Christian; Crumpler, Larry S.; Grant, John A.; Jolliff, Bradley L.; Arvidson, Raymond E.; et al.
Abstract: We report the results of geological studies by the Opportunity Mars rover on the Endeavour Crater rim. Four major units occur in the region (oldest to youngest): the Matijevic, Shoemaker, Grasberg, and Burns formations. The Matijevic formation, consisting of fine‐grained clastic sediments, is the only pre‐Endeavour‐impact unit and might be part of the Noachian etched units of Meridiani Planum. The Shoemaker formation is a heterogeneous polymict impact breccia; its lowermost member incorporates material eroded from the underlying Matijevic formation. The Shoemaker formation is a close analog to the Bunte Breccia of the Ries Crater, although the average clast sizes are substantially larger in the latter. The Grasberg formation is a thin, fine‐grained, homogeneous sediment unconformably overlying the Shoemaker formation and likely formed as an airfall deposit of unknown areal extent. The Burns formation sandstone overlies the Grasberg, but compositions of the two units are distinct; there is no evidence that the Grasberg formation is a fine‐grained subfacies of the Burns formation. The rocks along the Endeavour Crater rim were affected by at least four episodes of alteration in the Noachian and Early Hesperian: (i) vein formation and alteration of preimpact Matijevic formation rocks, (ii) low‐water/rock alteration along the disconformity between the Matijevic and Shoemaker formations, (iii) alteration of the Shoemaker formation along fracture zones, and (iv) differential mobilization of Fe and Mn, and CaSO4 ‐vein formation in the Grasberg and Shoemaker formations. Episodes (ii) and (iii) possibly occurred together, but (i) and (iv) are distinct from either of these. Key Points: Endeavour Crater impact rocks record multiple alteration episodes in early Mars history, spanning the Noachian to Early Hesperian The Shoemaker formation consists of polymict impact breccias that formed the continuous ejecta blanket of Endeavour Crater The Matijevic formation, a fine‐grained clastic sediment, is a preimpact lithology upon which the Shoemaker formation was deposited